American Academy of Ophthalmology 2015 Annual Meeting - Sonnenreich, Peter (P T, 2016)
The 119th annual meeting of the American Academy of Ophthalmology attracted 28,000 attendees. The authors review key scientific sessions on endophthalmitis, new patient education videos, and ongoing research activities.